2021
DOI: 10.3390/brainsci11030401
|View full text |Cite
|
Sign up to set email alerts
|

Parental Education and Left Lateral Orbitofrontal Cortical Activity during N-Back Task: An fMRI Study of American Adolescents

Abstract: Introduction. The Orbitofrontal Cortex (OFC) is a cortical structure that has implications in cognition, memory, reward anticipation, outcome evaluation, decision making, and learning. As such, OFC activity correlates with these cognitive brain abilities. Despite research suggesting race and socioeconomic status (SES) indicators such as parental education may be associated with OFC activity, limited knowledge exists on multiplicative effects of race and parental education on OFC activity and associated cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 134 publications
(202 reference statements)
1
5
0
Order By: Relevance
“…44 Our finding reflects MDRs of parental education on children's sleep problems in Black and Latino families. This is in line with what is already established on the MDRs of many economic resources such as parental education on impulsivity, 15 reward responsiveness, 40 inhibitory control, 45 attention, 46 and ADHD 26 for non-Latino Black children compared to non-Latino White children. Similar MDRs are also reported for the effects of almost all SES indicators on behavioral risks such as substance use 17 , unhealthy diet, 27 lack of exercise, 28 anxiety, 25 depression, 19 and suicide.…”
Section: Discussionsupporting
confidence: 90%
“…44 Our finding reflects MDRs of parental education on children's sleep problems in Black and Latino families. This is in line with what is already established on the MDRs of many economic resources such as parental education on impulsivity, 15 reward responsiveness, 40 inhibitory control, 45 attention, 46 and ADHD 26 for non-Latino Black children compared to non-Latino White children. Similar MDRs are also reported for the effects of almost all SES indicators on behavioral risks such as substance use 17 , unhealthy diet, 27 lack of exercise, 28 anxiety, 25 depression, 19 and suicide.…”
Section: Discussionsupporting
confidence: 90%
“…In the ABCD data, we have found weaker SES effects on the function and size of the thalamus (Assari & Curry, 2021), hippocampus , amygdala (Assari, Boyce, et al, 2020b), and cortical surface (Assari, 2020g;Assari, Boyce, Bazargan, et al, 2021;Assari, Boyce, Saqib, et al, 2021) for Black children compared to their White counterparts. Studies have also suggested that exposure to stress caused by a variety of causes such as life events , financial instability (Assari, 2020k), and race/ethnicity explain the observed MDRs for Black adolescents.…”
Section: Marginalization-related Diminished Returns (Mdrs)mentioning
confidence: 72%
“…At a cognitive level, there are weaker SES effects for emotion regulation, inhibitory control, reward processing, and executive function for Blacks compared to Whites (Assari, 2020cAssari, Boyce, Akhlaghipour, Bazargan, & Caldwell, 2020;Assari, Boyce, & Bazargan, 2020a. Cross-sectional analyses of the ABCD study data shows weaker effects of SES on the function/size of the thalamus (Assari & Curry, 2021), hippocampus , amygdala (Assari, Boyce, et al, 2020b), and cerebral cortex (Assari, 2020g;Assari, Boyce, Bazargan, et al, 2021;Assari, Boyce, Saqib, Bazargan, & Caldwell, 2021) for Black children compared to White children.…”
Section: Marginalization-related Diminished Returns (Mdrs)mentioning
confidence: 96%
“… 48 Several studies have shown that the OFC is associated with race, low socioeconomic status, stress and other factors associated with childhood trauma. 49 …”
Section: Discussionmentioning
confidence: 99%